KONSTRUKSI POSISI PEREMPUAN DALAM SURAT KABAR LOKAL (Analisis Framing Terhadap Feature “Tapaleuk” Kolom Berbahasa Daerah Kupang, dalam Surat Kabar Harian Pos Kupang, Mengenai Perempuan, edisi Januari-Juni 2016) (Verba Vitae Unwira, 2020)
The Construction of Woman's Position in Local Newspaper (A Framing Analysis on The Feature 'Tapaleuk', A Column Written in Local Language of Kupang In the Pos Kupang Newspaper, Dealing with Woman, Published in January To June Of 2016 Editions)The main problem examined in this study is on how Pos Kupang, one of the Local Newspapers in East Nusa Tenggara province,  constructs women's positions in one of its columnscalled Tapaleuk ? The academic significance of this study is to analyzethe contents of the news textsof the column by using the theory of media reality construction, framing, gender, and features. Practically, this study provides input for print media ownersas well as journalists about gender perspective based of the print media coverage. The results of this study indicate that the news text packaging of the column posit women in a proportional way. The texts describe and treat womanas a more dominant figure and not a victim. The existence of women is taken into account in social discourse and consensus. This fact is believed to emerge as  the result a change of view toward patriarchal societies which often places women as second class. The news texts of TAPALEUK seemmore advanced or modern as they ignore stereotypes against women. Thus readers get a fair view toward women. This very view may help people avoid those who tend to hold their hegemonic positions in social life.
Keywords: Local Newspaper; News; Gender; Construction; framing